Animal Ethics and India: Understanding the Connection through the Capabilities Approach - Chakraborty, Rhyddhi (Bangladesh Journal of Bioethics, 2017)
This paper, unveiling the visionary short-sightedness of animal protection, argues for a just vision towards animals in India. Critically analysing the wide range of animal protections in India, the paper finds that in spite of such protections, animals continue to suffer out of unfair and unjust treatments in the country. Considering visionary short-sightedness as the reason behind these unfair and unjust treatments, the paper argues that ensuring the rights of non-human animals to basic capabilities is a fundamental and just vision towards delivering ethical and just actions towards animals. For this, the paper grounds itself on the theoretical foundation of the capabilities approach and makes some policy-level recommendations to protect animals in India.